(untitled) (Itinera, 2019)
Focusing on the four years long, large-scale EU project Be SpectACTive!, the authors observe its initial, artistic and strategic, aims and the results in the light of the recent social and political changes as well as the notion of “inter-locality”. The EU priority Audience Development (AD) program and the organizations involved are analyzed highlighting successes and failures as well as their impact on cultural organizations and artists who have taken part in the program.